SOME FIXED POINT RESULTS FOR GENERALIZED CONTRACTIONS IN PARTIALLY ORDERED CONE METRIC SPACES - Asadi, M.; Soleimani, H. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2015)
The aim of this paper is to present some fixed point theorems for generalized contractions by altering distance functions in a complete cone metric spaces endowed with a partial order. We also generalize fixed point theorems of J. Harjani, K. Sadarangani [J. Harjani, K. Sadarangani, Generalized contractions in partially ordered metric spaces and applications to ordinary differential equations, Nonlinear Analysis 72 (2010) 1188-1197] from metric spaces to cone metric spaces.